School success in socially disadvantaged contexts: an analysis based on the Enem test - Nascimento, Matheus Monteiro (2020)
The reasons behind a child’s good performance at school are very complex. Given the multiple forms of family configuration, cases of school success in unfavorable social contexts are possible, even if statistically improbable. For this reason, this study aims to quantitatively analyze the profile of candidates who had a satisfactory performance in the Enem test despite their adverse economic and social situation. To that end, we used a database consisting of microdata from Enem 2009, which includes candidates’ answers to a socioeconomic questionnaire. Methodologically, we used statistical methods combined with theoretical framework in the field of sociology of education, such as Pierre Bourdieu and Bernard Lahire. The results suggest that candidates’ family size, taste for reading and interest in politics are factors significantly associated with a good performance in the Enem test.